HARMONIZATION OF MANAGEMENT PROCESSES IN THE PUBLIC SECTOR AS AN ACTUAL TREND OF THE NEW GENERATION OF POWER - M. Bespamiatnova (Вестник университета)
The key objective of this study is to analyse the concept of harmonization of the functions of public administration institutions and to identify the principles and characteristics of harmonious management applicable in the management structures of the public sector, as well as the prospects for improving the efficiency of its activities. The research is applied in nature. Within the study, the author carries out the analysis of various management models, as well as a comparative analysis of their interaction in the format of the concept of harmonious management. In addition, the article presents the results of the analysis of the vectors of application of the concept of harmonious management, which can be adapted to the organizations of the public sector; raises the issue of the content of the harmonization process and its stages. The article formulates the target guidelines for the application of the management harmonization concept in the public sector, proposals and conclusions on various variations and features of approaches to management harmonization. This paper is based on the analysis of foreign scientific literature, regulatory and analytical documents, as well as their synthesis, systematization, comparative analysis, and the study of specific cases. The author conducts an empirical study using the method of quantitative standardization of expert opinions. In addition, the article uses the visualization method.